PROTON MAGNETIC RESONANCE STUDIES OF PORPHYRIN IRON (III) CYANIDES - Wüthrich, K. (1969)
The nuclear magnetic resonance (NMR) spectra at 220 Mc of cyanodeuteroporphyrin IX dimethyl ester iron (III), cyanoprotoporphyrin IX diethyl ester iron (III), and cyanoprotoporphyrin IX iron (III) in a mixed solvent of 80 per cent d(5)-pyridine and 20 per cent D(2)O have been measured. The resonances are assigned and, except for the ester alkoxy groups, are shown to be shifted by temperature-dependent hyperfine interactions with Fe (III). From the experiments, upper limits are placed upon the pseudocontact contributions, and values of the contact interactions are derived. Spin densities in carbon π-orbitals are calculated from the contact shifts and discussed in terms of preliminary Hückel calculations.